2007
DOI: 10.1097/01.nur.0000299617.51722.fd
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Nursing Grand Rounds in a Community Hospital

Abstract: As a designate Magnet hospital, our Advanced Practice Council established a forum to promote and demonstrate excellence in nursing. The attributes of advanced practice nursing are the cornerstone to successful implementation of Nursing Grand Rounds. The involvement of clinical nurses across the 5 stages of proficiency in skill acquisition is a means to retain clinical experts and foster the development of nurses from novice to expert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Since then, published literature on the use of NGR in the hospital setting have been scarce. More recently, with (a) the advent of the Magnet™ Program in the U. S., (b) the Institute of Medicine's (2010) report addressing continuing education for health professions, and (c) recommendations from the Carnegie Report (Benner, Sutphen, Leonard, & Day, 2010), (Armola et al, 2010;Furlong, D'Luna-O'Grady, Macari-Hinson, O'Connel, & Pierson, 2007;Hagle & Millenbruch, 2011;Iacono, 2008;Lannon, 2005;Wolak, Cairns, & Smith, 2008 …”
mentioning
confidence: 96%
“…Since then, published literature on the use of NGR in the hospital setting have been scarce. More recently, with (a) the advent of the Magnet™ Program in the U. S., (b) the Institute of Medicine's (2010) report addressing continuing education for health professions, and (c) recommendations from the Carnegie Report (Benner, Sutphen, Leonard, & Day, 2010), (Armola et al, 2010;Furlong, D'Luna-O'Grady, Macari-Hinson, O'Connel, & Pierson, 2007;Hagle & Millenbruch, 2011;Iacono, 2008;Lannon, 2005;Wolak, Cairns, & Smith, 2008 …”
mentioning
confidence: 96%
“…[7][8][9] Wolak et al 10 discovered that presentations in NGRs were an effective format to improve knowledge acquisition. Furlong et al 11 identified their NGRs as an opportunity for nursing expertise to be shared, a process that promoted professional development. For all of these reasons, we decided to try NGRs as a tool to enhance nursing practice.…”
Section: Introductionmentioning
confidence: 99%
“…As others hear of your interests and expertise, you may find yourself invited to present a Grand Rounds to multiple disciplines. Grand Rounds are ready‐made “to foster networking among diverse clinical nursing specialty areas” through a social learning environment (Furlong, D'Luna‐O'Grady, Macari‐Hinson, O'Connel, & Pierson, , p. 288).…”
Section: Networking At Homementioning
confidence: 99%